2005
DOI: 10.1158/0008-5472.can-04-2802
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Organization of Amplified MYC Genes Suggests Distinct Mechanisms of Amplification in Tumorigenesis

Abstract: Integration of the human papillomavirus (HPV) genome into the host genome is associated with the disruption of the HPV E2 gene and with amplification and rearrangement of the viral and flanking cellular sequences. Molecular characterization of the genomic structures of coamplified HPV sequences and oncogenes provides essential information concerning the mechanisms of amplification and their roles in carcinogenesis. Using fluorescent hybridization on stretched DNA molecules in two cervical cancer-derived cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 45 publications
5
35
0
1
Order By: Relevance
“…The red rectangles below the X-axis localize the different amplimers used. with the pattern of the co-amplified MYC and viral sequences on DNA stretched molecules previously reported (Herrick et al, 2005), clearly indicate that, in the genital tumors analysed, integration of viral DNA occurred prior to gene amplification. In two cases, both associated with HPV18, MYC was overexpressed but not amplified.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The red rectangles below the X-axis localize the different amplimers used. with the pattern of the co-amplified MYC and viral sequences on DNA stretched molecules previously reported (Herrick et al, 2005), clearly indicate that, in the genital tumors analysed, integration of viral DNA occurred prior to gene amplification. In two cases, both associated with HPV18, MYC was overexpressed but not amplified.…”
Section: Discussionsupporting
confidence: 79%
“…Northern blot experiments showed that MYC was overexpressed in IC1 cells. More recently, using DNA stretching (Herrick et al, 2005), we found that MYC was co-amplified together with HPV18 DNA sequences in IC1 cells. These data suggest that MYC activation could be secondary to the insertion of HPV DNA sequences at the MYC locus.…”
Section: Introductionmentioning
confidence: 94%
“…2D). This fact points to an unequal sister chromatid homologue recombination as the initial amplification mechanism (30,31). It is possible that the inverted Alus found near the telomeric breakage point confer instability to this region, promoting complementary interactions in the same strand and facilitating a hairpin or a secondary structure formation leading to a unequal recombination between chromatids ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…They also seem to occur early, as we analyzed integration sites after only f25 population doublings in feeder-free conditions. Local rearrangement has been described in previous cell line studies (29,44,45), but it is likely to have been underreported, particularly in clinical samples, as PCR-based methods of integration site analysis would not identify it. Interestingly, it has recently been shown that latent integrants may be able to induce genomic instability in the locality of the integration site, despite no quantitative deregulation of E6 and E7, as expression of E1 and E2 proteins in cells containing integrated HR-HPV origins can induce genomic rearrangements of flanking ACAGTGCTACATTATTAAG None *The sequences were determined at the DNA level by RS-PCR, except in the case of clones Z, E3, O2, and G2 where the host-viral junction of the fusion transcript is given, as determined by APOT.…”
Section: Discussionmentioning
confidence: 99%